1999
DOI: 10.1074/jbc.274.46.32757
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Protein Substrates by Protein-disulfide Isomerase

Abstract: Refolding of partially folded mitochondrial malate dehydrogenase (mMDH) is assisted by protein-disulfide isomerase (PDI).It is shown that the fluorescence probe is covalently attached to a SH residue located in the b domain. Based on the fluorescence measurements of native and derivatized PDI, it is suggested that recognition of the unfolded substrate involves conformational changes propagated to several domains of PDI. Protein-disulfide isomerase (PDI)1 is a multifunctional enzyme that both catalyzes the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Moreover, PDI could not reverse the aggregation of MDH when added in 7-fold molar excess over MDH ( Figure 4C ). MDH is used as a model aggregation-prone substrate for the activity of molecular chaperones such as PDI ( Cheung and Churchich, 1999 ; Goloubinoff et al, 1999 ; Nillegoda et al, 2015 ), but it does not form amyloid structures. The aggregation of MDH is therefore detected by light scattering instead of ThT fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PDI could not reverse the aggregation of MDH when added in 7-fold molar excess over MDH ( Figure 4C ). MDH is used as a model aggregation-prone substrate for the activity of molecular chaperones such as PDI ( Cheung and Churchich, 1999 ; Goloubinoff et al, 1999 ; Nillegoda et al, 2015 ), but it does not form amyloid structures. The aggregation of MDH is therefore detected by light scattering instead of ThT fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The a and a’ domains allow PDI to function as an oxidoreductase, but this enzymatic activity is not required for PDI to act as a chaperone [20,21]. The b and b’ domains at the base of the U-shaped protein serve as the main sites of substrate binding [22,23,24]. The x linker is an unstructured segment that contributes to the conformational flexibility of PDI, while the c region contains a KDEL tag that retains PDI in the ER [25].…”
Section: Introductionmentioning
confidence: 99%
“…The x linker is an unstructured segment that contributes to the conformational flexibility of PDI, while the c region contains a KDEL tag that retains PDI in the ER [25]. Interactions at one domain of PDI influence the structure/function of other PDI domains [24,25,26,27,28]. PDI also undergoes redox-dependent conformational changes that can influence its interactions with select substrates [29].…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation constant, K d , for the binding reaction of GAPDH folding intermediates with PDI at 25.0 °C, 30.9 n m , is six‐fold that with GroEL at the same temperature. Recently, Cheung and Churchich [38] reported that PDI binds with the malate dehydrogenase folding intermediate with a K d of 0.2 µ m , which is fivefold the dissociation constant for the interaction of GroEL with the same substrate. Generally, GroEL binds with its substrate to form a stable complex, which does not dissociate unless ATP is added.…”
Section: Discussionmentioning
confidence: 99%